2005
DOI: 10.1086/429245
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunospot Assay Responses to Early Secretory Antigenic Target 6, Culture Filtrate Protein 10, and Purified Protein Derivative among Children with Tuberculosis: Implications for Diagnosis and Monitoring of Therapy

Abstract: Tuberculosis-specific ELISPOT testing is a promising tool that should be evaluated as a potential diagnostic test for childhood tuberculosis. We caution against the use of an early decrease in response as a marker of successful antituberculous chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 15 publications
(24 reference statements)
11
72
0
4
Order By: Relevance
“…In some cases, the initially negative T SPOT TB results become positive in the process of monitoring, which supports the above hypothesis [15][16][17].…”
Section: Diagnostic Value Of T Spot Tb In Infant To 5-year Old Childrsupporting
confidence: 78%
“…In some cases, the initially negative T SPOT TB results become positive in the process of monitoring, which supports the above hypothesis [15][16][17].…”
Section: Diagnostic Value Of T Spot Tb In Infant To 5-year Old Childrsupporting
confidence: 78%
“…LIEBESCHUETZ et al [19] reported a sensitivity of 83% for T-SPOT.TB in African children. NICOL et al [20] described T-SPOT.TB positive results in 70% of children with clinical TB. False negative results of both tests in active TB have been described previously [6,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…constitue le gold standard dans le diagnostic de la tuberculose pulmonaire et ou pleurale chez l'adulte [25].…”
Section: Aspects Chirurgicaux Des Complications Des Tuberculosesunclassified